Challenges to collaborative forest management and their impact on strengthening forest-dependent communities in Bara District, Nepal - Adhikari, Ishwori; Ghimire, Pramod; Lamichhane, Uchita (Journal of Forests, 2025)
Collaborative forest management (CFM) is a widely endorsed approach for achieving sustainable forest management, emphasizing inclusive participation and equitable benefit-sharing among stakeholders. In Nepal, however, the effectiveness of CFM is often constrained by institutional, socio-economic, and policy-related challenges that adversely affect forest-dependent communities. This study aims to identify and evaluate the key barriers to effective CFM and examine their implications for enhancing the resilience of these communities in Badhnihar Collaborative Forest in Parsa district, Nepal. Data were collected using a forest user survey (n=144), field observation, and focus group discussions, integrating both qualitative and quantitative tools, including perception analysis using a Likert scale and socio-economic indicators. The findings show major constraints, with limited institutional capacity (65.25% of respondents), inadequate funding (47.95%), and political interference (61.75%) emerging as the most significant barriers to successful collaboration. These challenges intensify socio-economic vulnerabilities by limiting access to forest resources and pushing communities to seek alternative livelihoods. In addition, factors such as gender roles and educational level influence both decision-making processes and access to resources, underscoring the need for inclusive and context-specific strategies. Notably, CFM initiatives have generated substantial employment, with 8,475 jobs through nursery establishments and 6,500 jobs through forest monitoring efforts. Thus, the study concludes that addressing these institutional and socio-political barriers is essential for enhancing community resilience and advancing sustainable forest management. Major recommendations include strengthening institutional frameworks, promoting equitable resource access, and integrating participatory approaches such as the local adaptation plan.